Fracturing Debate? A Review of Research on Media Coverage of “Fracking” - Matthews, Julian; Hansen, Anders (Frontiers in Communication, 2018)
Hydraulic fracturing is an energy extraction process that is increasingly attracting controversy. This article seeks to outline how the media report hydraulic fracturing (or “fracking”), and to explore its place within the reporting of energy concerns generally. To this end, it draws on an environmental communication perspective to understand the media reporting of the issue and the processes that shape it. This review reveals that media reporting of fracking is partitioned broadly according to discussions of the economic benefits or the environmental risks associated with the process. Further, these observed patterns in the reporting appear to mirror the recognized claims made about the issue, and the influence from protests and online media alongside national polity on energy production and security. While there is evidence that the practices of journalists and the geographic, economic and political contexts of their news production environments shape the amounts and the types of news reporting, the publics' perceptions appear, somewhat knowledgeable, but largely ambivalent or undecided on the issue at present. Therefore, it is argued that future research must continue to examine the reporting of hydraulic fracturing, its context, production, and its wider reception to develop our understanding of the role of the media in national conversations on fracking, energy, and the environment.